Development of Physics E-LKPD Using Augmented Reality (AR) Based LOK-R ‎Model on Students' Critical Thinking Skills - Rizka Dwi Maretha‎; Irwandani; Vandan Wiliyanti (Yayasan Darussalam Bengkulu, 2025)
This study was conducted to develop an Electronic Student Worksheet (E-LKPD) based on Augmented Reality (AR) with the LOK-R (Literacy, Orientation, Collaboration, Reflection) model for Physics on thermodynamics material for grade XI students and to test its effectiveness in improving students' critical thinking skills. The research method used was Research and Development (R&D) with the 4D development model, but limited to the development stage (3D). Data collection methods involved non-test instruments (observation sheets and questionnaires) and a 10-item essay test. The results of the study indicate that: (1) The AR-based Physics E-LKPD with the LOK-R model is highly suitable for use in thermodynamics learning for high school students with a